THE EFFECT OF COMMITMENTS AND ORGANIZATION TRANSFORMATIONAL LEADERSHIP ON TEACHER ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (Economic and Bussiness Faculty, Dr Soetomo University, 2016)
Abstract.quantitative correlation study took 18teachersampling junior high schoolThoriqotunNajahSingosariMalang.The data collection technique using a questionnaire that has been tested the validity and reliability test. Data analysis technique used isAnalisia, multiple linear regression correlation the results obtained Fcount = 86.818 is greater than the Ftable: 0,05; 2; 18 by dk v1 = 2 and v2 = 18, the score of 3.554557 or with a significance level of 0.000 (p <0.05), the regression model, namely variable transformational leadership and organizational commitment together can be used to predict the organizational citizenship behavior Master Junior ThoriqotunNajahSingosariMalang..